(untitled) (Indian Journal of Engineering and Materials Sciences (IJEMS), 2023)
In this study, a double-sided sheet hydroforming (DSH) test system which contains dies, sealing, pressure intensifiers and control unit is designed, built and tested. The hydraulic numerical control system which is currently used is modified as four axis where parameters are forming pressure, back pressure, punch position and blank holder force. A hydromechanical deep drawing press is modified in terms of die and sealing. New sealing components are used to prevent leakage during forming process, because one side of the sheet is exposed to the forming pressure and other side is exposed to both the back pressure and the moving punch. Performance tests are carried out to determine the limitations and capacity of the system. After the performance tests, it is concluded that; the higher forming rates all along the process curve, the higher pressure and force differences. However, the resultant error of the corresponding points is only higher at the beginning of the process curve. In addition, the higher slopes in process curves increase the pressure and force differences. A conical industrial part was deformed by using hydromechanical deep drawing and DSH processes to test performance of the DSH press. The wrinkling defect that occurred in previous hydroformed parts was reduced remarkably by using back pressure in DSH process. As a result, double-sided sheet hydroforming test press was been successfully designed and manufactured. Finally, this study provides a technical knowledge and can be used as a guideline for the design and performance evaluation of similar manufacturing systems.